Internal Control, Organizational Commitment, and Morality on Fraud Prevention: The Role of Leadership Style - Ghaitsya Zahira; Fefri Indra Arza (Universitas Sains dan Teknologi Komputer, 2026)
This study examines the influence of internal control systems, organizational commitment, individual morality, and leadership style on fraud prevention in regional financial management, specifically within the Padang City Government. Utilizing a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis, this research tested seven hypotheses involving both direct and moderating effects. Data were collected from 100 civil servants directly involved in regional financial management across various Satuan Kerja Perangkat Daerah (SKPD) in Padang City. The results demonstrate that internal control systems (β = 0.332, t = 5.864, p = 0.000), organizational commitment (β = 0.232, t = 3.629, p = 0.000), individual morality (β = 0.234, t = 4.149, p = 0.000), and leadership style (β = 0.286, t = 5.195, p = 0.000) all have significant direct positive effects on fraud prevention. However, leadership style does not function as a moderating variable for the effects of the three independent variables on fraud prevention. The model demonstrates strong explanatory power with R² = 0.739 (adjusted R² = 0.727), indicating that 73.9% of the variation in fraud prevention is explained by these variables. These findings suggest that effective fraud prevention strategies in regional financial management require simultaneous strengthening of formal control mechanisms, development of civil servants' moral character, enhancement of organizational commitment, and cultivation of integrity-driven transformational leadership. The study contributes to understanding fraud prevention within the Indonesian public sector context and provides practical recommendations for governance improvements in regional financial management.